Cost Efficiency of the oil and gas industry in nigeria: Data Envelopment Analysis. - TAFAMEL, Andrew Ehiabhi; Akrawah, Onutomaha Dennis (Archives of Business Research, 2015)
ABSTRACT In this study, we investigated the profitability and cost efficiency of oil and Gas companies in Nigeria from 2012-2013. This study used a sample of 9 quoted Oil and Gas companies in Nigeria that have consistently published their audited annual financial report between the periods under study. We adopted a Data Envelopment Analysis to test the efficiency of the various companies under Variable Returns to Scale (VRS), Constant Return to Scale (CRS) and Scale efficiency. In analyzing the inputs outputs further, we conducted descriptive statistics and correlation analysis. The Results show that Caverton Offshore Plc, Eternal Oil and Gas, Japaul Mobile and Total are good benchmarks in the oil and Gas industry in Nigeria were all efficient in the Scale efficiency test. Also Oando is scale efficient though it was not in the case of CRS. This study revealed that that only the very big oil and gas companies will have enough inputs to generate revenue and gross profit. The study recommended that management and concerned authorities of the oil and gas companies in Nigeria should implement sound policies that would ensure that the sector is efficient. It is therefore suggested that more resources should allocate for the oil and gas sectors for more returns with improved cost efficiency. Keywords: Oil and Gas industry, Cost Efficiency, Data Envelopment Analysis, Labour and Capital, profitability.